PENGARUH MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT.JASA RAHARJA (PERSERO) CABANG BALI - Gerry Dwi Handara, Made; Mujiati, Ni Wayan (E-Jurnal Manajemen; Vol 2 No 11 (2013), 2013)
Insurance company need a boost and just leader and dedicated a job in order to maximize the potential of employees that have an impact on employee job satisfaction. Response from employees job satisfaction indicated by several aspect: the level of attendance, responsibility for work, timely completion of work and the positive reaction to the company policy. This study aims to answer the research question (research) is whether job satisfaction is influenced by motivation and leadership styles. The analytical method used was multiple linear analysis techniques. The result showed simultaneous motivation and leadership styles have a significant effect. In partial motivation and leadership style, and a strong effect on employee job satisfaction. Keywords: Motivation, Leadership Style, Job Satisfaction